2015
DOI: 10.1159/000371390
|View full text |Cite
|
Sign up to set email alerts
|

Is Chemoradiotherapy Beneficial for Stage IV Rectal Cancer?

Abstract: Purpose: The aim of this study was to investigate the oncologic impact of preoperative or postoperative chemoradiotherapy on stage IV rectal cancer. Methods: A total of 140 consecutive patients with locally advanced mid-to-lower rectal cancer and resectable stage IV disease were prospectively enrolled. In total, 69 patients received chemoradiotherapy (26 preoperatively and 43 postoperatively); in contrast, 71 did not. Survival curves were constructed using the Kaplan-Meier method, and a multivariate analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Indeed, stage IV rectal cancers comprise a heterogeneous group, which impedes the progress of prospective studies. Several studies with small sample size compared of local recurrence rate and overall survival of stage IV rectal cancer patients with or without neoadjuvant chemoradiotherapy and the results are inconsistent 11-14. In the present study, we demonstrated that patients with resectable rectal cancer received radiotherapy before definitive primary resection surgery had better prognosis than radiotherapy after surgery using a relative large-population bases database.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Indeed, stage IV rectal cancers comprise a heterogeneous group, which impedes the progress of prospective studies. Several studies with small sample size compared of local recurrence rate and overall survival of stage IV rectal cancer patients with or without neoadjuvant chemoradiotherapy and the results are inconsistent 11-14. In the present study, we demonstrated that patients with resectable rectal cancer received radiotherapy before definitive primary resection surgery had better prognosis than radiotherapy after surgery using a relative large-population bases database.…”
Section: Discussionmentioning
confidence: 50%
“…Huh et al 11 reported the outcomes of 69 patients received chemoradiotherapy and 71 patients did not. They found that preoperative radiotherapy improved local control of metastatic rectal cancer while postoperative radiotherapy did not.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we find several reports demonstrated chemoradiotherapy prefer to have higher benefits in improving local control rather than OS. A recent study found that rectal cancer patients received radiotherapy had an improved local control, however, that was not significantly in improving OS (27). Additionally, patients with postoperative radiotherapy were observed to have reduced local recurrence rate in rectal cancer (28,29).…”
Section: Discussionmentioning
confidence: 97%
“…Most series include patients who had non-surgical management of synchronous metastasis and differences in timing of radiotherapy (10,(15)(16)(17)(18)(19)(20). The most relevant comparisons to our work involve two studies, which investigated the value of RT in patients undergoing curative surgery.…”
Section: Discussionmentioning
confidence: 99%